2012
DOI: 10.2164/jandrol.111.015529
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Fas/Fas‐L and Bax/Bcl‐2 Systems in Germ Cell Death Following Immunization With Syngeneic Testicular Germ Cells in Mice

Abstract: Experimental autoimmune orchitis (EAO) is characterized by T cell-dependent lymphocytic inflammation and seminiferous tubule damage, which can result in the death of germ cells. The aim of the present study is to investigate the roles of the Fas/ Fas-L and Bax/Bcl-2 systems in the death of germ cells in mice with EAO that is induced by immunization with syngeneic testicular germ cells (TGC). The results using real-time reverse transcriptionpolymerase chain reaction and immunostaining show that many terminal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Th1 cells (involved in delayed-type hypersensitivity) produce TNF-α and IFN-γ, whereas Th2-cells (involved in humoral immunity) produce IL-6 and IL-10 [13, 14]. Apoptosis is one of the main features characterizing germ cell death in the testes and is mediated by the Fas/Fas-L systems [15, 16]. Quantitative real-time PCR was performed in duplicate in a TP800 Thermal Cycler Dice Real Time System (TaKaRa), and the comparative C t method (2∆∆C t ) was used to quantify gene expression levels.…”
Section: Methodsmentioning
confidence: 99%
“…Th1 cells (involved in delayed-type hypersensitivity) produce TNF-α and IFN-γ, whereas Th2-cells (involved in humoral immunity) produce IL-6 and IL-10 [13, 14]. Apoptosis is one of the main features characterizing germ cell death in the testes and is mediated by the Fas/Fas-L systems [15, 16]. Quantitative real-time PCR was performed in duplicate in a TP800 Thermal Cycler Dice Real Time System (TaKaRa), and the comparative C t method (2∆∆C t ) was used to quantify gene expression levels.…”
Section: Methodsmentioning
confidence: 99%
“…291 The pro-inflammatory cytokines, TNF and IFNγ, FAS and FASL, and NOS2 have been identified as potential causative factors in the development of orchitis, principally by stimulating antigen-presentation activity and spermatogenic cell apoptosis. 595,[890][891][892][893][894] Although IL6 production by testicular macrophages increased during experimental autoimmune orchitis in rats, 895 and was implicated in the disruption of the inter-Sertoli cell tight junctions, 896 administration of IL6 has been shown to inhibit the progression of orchitis in LPS-resistant mice. 897 The progression of orchitis may also be inhibited by IL10 and by androgens.…”
Section: Experimental Autoimmune Orchitismentioning
confidence: 99%
“…Bcl-2 is an antiapoptotic gene, and its protein is present as a buffy particle with strong expression in normal cells but is present in very low concentrations or absent in the cytoplasm of apoptotic cells [ 21 ]. A significant increase in the positive expression of Bcl-2 proteins (darker color) was observed in the GCs of normal control rats ( Figure 3(a) ), the Menoprogen group ( Figure 3(c) ) and Progynova group ( Figure 3(h) ), compared with the negative expression in NAM group ( Figure 3(b) ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Bcl-2 expression in the Progynova group was higher than in the Menoprogen group showing that Progynova reduced GC apoptosis better than Menoprogen ( Figure 3(d) ). Bax is a proapoptotic molecule, and Bax proteins are more highly expressed in apoptotic cells than in normal cells [ 21 ]. In this study, the GCs from normal control rats weakly expressed Bax proteins as shown in Figure 3(e) by a lighter color.…”
Section: Resultsmentioning
confidence: 99%